2020
DOI: 10.1111/and.13539
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐4485‐3p expression reduced in spermatozoa of men with idiopathic asthenozoospermia

Abstract: Asthenozoospermia (AZS), which characterised by reduced forward sperm motility, is a common cause of male infertility. Recently, mitochondrial dysfunction reported in AZS men came to attention for finding the molecular aetiology of AZS. Mitochondria‐related microRNAs (miRNAs) are the most important regulators of mitochondrial function through post‐transcriptionally modulation of gene expression. Therefore, this study aims to evaluate the expression of four recently reported mitochondrial‐related miRNAs (miR‐44… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…In patients with asthenozoospermia, characterized by a reduction in sperm motility, the relative content of PARK7 is lower in both ejaculated sperm [ 19 , 24 ] and seminal plasma [ 25 ]. In addition, PARK7 has been identified as a target of miR-4485-3, whose downregulation has also been associated to asthenozoospermia [ 26 ]. Under oxidative stress conditions associated with asthenozoospermia, PARK7 has been observed to be translocated from the equatorial segment to the midpiece, which has been proposed as a possible protective mechanism for sperm to maintain their mitochondrial function [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with asthenozoospermia, characterized by a reduction in sperm motility, the relative content of PARK7 is lower in both ejaculated sperm [ 19 , 24 ] and seminal plasma [ 25 ]. In addition, PARK7 has been identified as a target of miR-4485-3, whose downregulation has also been associated to asthenozoospermia [ 26 ]. Under oxidative stress conditions associated with asthenozoospermia, PARK7 has been observed to be translocated from the equatorial segment to the midpiece, which has been proposed as a possible protective mechanism for sperm to maintain their mitochondrial function [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study on mitochondrial microRNAs demonstrated that miR‐4485‐3p expression level was reduced in semen samples of asthenozoospermic patients compared with fertile men. They also found that the dynein heavy chain 1 gene (DNAH1), KIT and parkinsonism‐associated deglycase (PARK7), regulated by miR‐4485‐3p, were associated with male infertility (Heidary et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…BDNF was detected in the head, neck, and tail of human spermatozoa [36], and exogenous BDNF at 0.133 nM could signi cantly in uence viability and motility of human sperm [37]. The expression of miR-4485 was signi cantly downregulated in the asthenozoospermia patients compared to controls, and KIT, which acts as its target gene, was related to male infertility by bioinformatic analysis [38]. These hub genes enriched in neurotrophin signaling pathway, indicating that they were critical for differentiation of nerve cells as well as playing critical roles in the development of reproductive system and the maintenance of spermatozoa normal function.…”
Section: Discussionmentioning
confidence: 97%